Compulsory outpatient treatment: a one-year follow-up study in Portugal - Brissos, Sofia (2017)
Abstract: Background: There is insufficient evidence regarding the impact of compulsory outpatient treatment (COT). Aims: We evaluated the impact of COT over one year on symptoms, personal and social functioning, insight and cognition. Methods: Naturalistic, longitudinal analysis, at baseline and one-year follow-up, of 15 patients followed in a specialized COT clinic. Patients underwent a standardized evaluation with the Positive and Negative Syndrome Scale (PANSS), Personal and Social Performance Scale (PSP), Berrios-Markova insight scale and Scale to Assess Unawareness in Mental Disorder (SUMD), Trails A and B, Digit Span, and the Controlled Oral Word Association Test (COWA). Results: At follow-up there was significant improvement in personal and social functioning (baseline total PSP: mean=46.9; follow-up: mean=59.3), and specifically in socially useful activities including work and study (p=0.012), and personal and social relationships (p=0.033). Three patients (20%) scored =>69 on the PSP, a good level of functioning. However, we found no significant improvements in symptoms (PANSS=56.8), subjective or objective insight (Berrios- Markova=10.0 and SUMD=11.0), or cognitive performance. Conclusions: At one-year follow-up, patients on COT showed significant improvement in personal and social functioning, specifically in socially useful activities including work and study and in personal and social relationships, but no improvement in symptoms, insight and cognitive functioning.